Identification and characterization of microRNAs in Humulus lupulus using high-throughput sequencing and their response to Citrus bark cracking viroid (CBCVd) infection - Mishra, Ajay Kumar; Duraisamy, Ganesh Selvaraj; Matoušek, Jaroslav; Radisek, Sebastjan; Javornik, Branka; Jakse, Jernej (BMC genomics, 2016)
BACKGROUND: Hop (Humulus lupulus L.) plants are grown primarily for the brewing industry and have been used as a traditional medicinal herb for a long time. Severe hop stunt disease caused by the recently discovered Citrus bark cracking viroid (CBCVd) is one of the most devastating diseases among other viroid infections in hop. MicroRNAs (miRNAs) are a class of non-coding small RNAs that play important roles in gene expression regulation. To identify miRNAs in hop and their response to CBCVd-infection, two small RNA (sRNA) libraries were prepared from healthy and CBCVd-infected hop plants and were investigated by high throughput sequencing. RESULTS: A total of 67 conserved and 49 novel miRNAs were identified. Among them, 36 conserved and 37 novel miRNAs were found to be differentially recovered in response to CBCVd-infection. A total of 311 potential targets was predicted for conserved and novel miRNAs based on a sequence homology search using hop transcriptome data. The majority of predicted targets significantly belonged to transcriptional factors that may regulate hop leaf, root and cone growth and development. In addition, the identified miRNAs might also play an important roles in other cellular and metabolic processes, such as signal transduction, stress response and other physiological processes, including prenylflavonoid biosynthesis pathways. Quantitative real time PCR analysis of selected targets revealed their negative correlation with their corresponding CBCVd-responsive miRNAs. CONCLUSIONS: Based on the results, we concluded that CBCVd-responsive miRNAs modulate several hormone pathways and transcriptional factors that play important roles in the regulation of metabolism, growth and development. These results provide a framework for further analysis of regulatory roles of sRNAs in plant defense mechanism including other hop infecting viroids in particular.
Keywords: Humulus lupulus; nemoci rostlin; Phenotype; Humulus; High-Throughput Nucleotide Sequencing; Citrus bark cracking viroid; Reproducibility of Results; messenger RNA; RNA rostlin; stanovení celkové genové exprese; microRNA; RNA, Messenger; RNA, Plant; Computational Biology; reprodukovatelnost výsledků; Target expression; Data Curation; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; vysoce účinné nukleotidové sekvenování; High-throughput sequencing; mikro RNA; Plant Diseases; Viroids; datové kurátorství; RNA Interference; MicroRNAs; fenotyp; RNA interference; výpočetní biologie; Gene Expression Profiling